THE CONCEPT OF HAPPINESS IN UKRAINIAN PROVERBS: PSYCHOCOGNITIVE AND LINGUOCULTURAL ASPECTS - Kalko, Valentyna; Kalko, Mykola (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. The article is concerned with the realization of the concept HAPPINESS in Ukrainian proverbs. The author analyzes the concept of HAPPINESS as one of the basic cultural concepts, the semantics of which is fixed on the linguistic, axiological, everyday, artistic levels of culture. Based on cognitive and linguocultural analysis, it has been proven that the notional figurative and evaluative content of the concept of HAPPINESS actualized in in the Ukrainian paremic picture of the world is productively verbalized. The purpose. The purpose of the article is a comprehensive analysis of the psychocognitive and linguistic cultural representation of the concept of HAPPINESS in the paremiic fund of the Ukrainian language in the projection on the functions and structures of ethnic consciousness. Main results of the study. The most significant value points connected with the concept “be happy” are revealed, it is noted that proverbs developed in collective consciousness of the Ukrainian people and were fixed in national mentality. The high quantitative fullness of HAPPINESS concept in Ukrainian proverbs is shown. It has been established that happiness is associated with the concepts of destiny, pleasure, wellbeing, virtue, good luck, between which there are interconceptual connections. It is established that the studied concept forms axiological, figurative and behavioural components of mentality of the Ukrainians. Originality. The article focuses on the ambivalent nature of the concept, the reasons for which the author sees in the binary nature of the Ukrainian mentality. The concept of HAPPINESS in the paremiic picture of the world of Ukrainians is a multi-functional, ambivalent, multi-dimensional entity that records vitalist guidelines. Its conceptual content is primarily related to good fortune, health, family, children, love, figurative formed as a result of metaphorical analogy with animals, birds, objects, valuable represented by a positive assessment as a state of complete satisfaction with life, a manifestation of joy. Awareness of happiness occurs against the background of opposite feelings – unhappiness, grief, trouble. Through the lens of conceptual metaphor theory, the research elucidates the various source domains used to map onto the target domain of HAPPINESS. Conclusions and specific suggestions of the author. Ideas about happiness and unhappiness partly form evaluative judgments about life in general, they determine the life strategy of an individual. The proverbs concept of happiness generally reflects the attitude of Ukrainians to the essence of life: it is primarily not only a dream value, but also a goal that an individual can achieve, acquire, build with his own efforts. Ukrainian proverbs reflect universal journey from adversity to happiness, resonating deeply with listeners facing challenges, highlight the transformative power of nature and human resilience but also underscore the collective aspect of experiencing and overcoming hardship.